Comparativo de sistemas construtivos: alvenaria estrutural x paredes de concreto moldadas in loco - Monteiro, Gabrielly Silva (2023)
This study aims to conduct a comparative investigation of the implementation of two construction systems: cast-in-situ concrete walls and structural masonry, in order to determine which system is more advantageous. With the need for rationalization, speed, and efficiency, the construction market had to find ways to maintain productivity at a high level. In this context, the cast-in-situ concrete walls construction method has been gaining prominence in Brazil. This work examines this system, its components, and execution, and also compares it with the structural masonry construction method. After conducting a qualitative and quantitative analysis and comparison of the two systems, it can be observed that, in comparison to structural masonry, the cast-in-situ concrete walls system stands out due to its advantages, such as speed and high productivity, which can reduce execution time by up to 30% compared to structural masonry. It also offers increased strength and durability, reduced labor requirements due to the multifunctionality of the teams, and less material waste, resulting in up to a 50% reduction in waste and relatively lower construction costs. Thanks to its quick execution, this system becomes excellent for large-scale projects, such as condominiums, due to its industrialization, playing a significant role in overall rationalization in the construction process.